Copenhagen Psychosocial “Work Organization and Job Content” as a Higher-Order Construct in Relation to Workers’ Health: The Moderating Role of Leadership Quality - Javaid MU; Sohail M; Bano S; Ibrahim AM (Dove Medical Press, 2023)
Muhammad Umair Javaid,1 Marva Sohail,2 Sobia Bano,3 Aidarus Mohamed Ibrahim4 1Department of Management Sciences, Lahore Garrison University, Lahore, Pakistan; 2Department of Psychology, Lahore Garrison University, Lahore, Pakistan; 3Department of Management Sciences, GIFT Business School, Gujranwala, Pakistan; 4College of Computing and IT, University of Hargeisa, Hargeisa, SomaliaCorrespondence: Aidarus Mohamed Ibrahim; Muhammad Umair Javaid, Email aidarusibrahim11@gmail.com; aidarus.ibrahim@uoh.edu.so; umairjav@yahoo.comOriginality/Purpose: The current study aims to investigate the novel approach of utilizing work organization and job content (WOJC) as a higher-order construct that is one of the domains of the Copenhagen Psychosocial Questionnaire (COPSOQ), examining its relationship with sleeping troubles and somatic stress, while also exploring the moderating effect of leadership quality.Sample/methods: Snowball sampling technique was used to collect the data in this study, with a population consisting of 360 workers employed in hazardous work environments at poultry feed mills. The structural equation modelling technique was applied to achieve the range of outcomes.Results: The results reveal that WOJC has a significant negative impact on both psychological (sleeping troubles) and physiological (somatic stress) health factors among poultry workers. Although leadership quality did not moderate the relationship between WOJC and physiological health factors, it did moderate the relationship between WOJC and psychological health factors.Conclusion/Implications: This study has significant implications for researchers, poultry feed mill owners, policymakers, and regulatory bodies. Additionally, the methodological contribution of utilizing WOJC as a higher-order construct provides unique insights for researchers.Limitations: Due to COVID-19 restrictions, the data was collected online from one province only; future studies should spread the sampling framework to all provinces with different domains of COPSOQ.Keywords: poultry, Copenhagen Questionnaire, somatic stress, sleeping trouble, leadership quality